ACHIEVING HIGH BAND SCORES IN THE IELTS LISTENING MODULE: A PRACTICAL TEACHING GUIDE - Safiya Solihova Azamatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: As it has been mentioned many times that The International English Language Testing System (IELTS) checks candidates’ English language based on their 4 different types of skills. These are reading, listening, speaking and writing. This article will examine listening module which assesses a candidate’s ability to comprehend spoken English across various contexts and accents. Actually, achieving a high band score requires a sophisticated understanding of active listening strategies and strong teaching methods. This article will provide an effective guide for educators and test-takers by focusing on key skills and strategies which are necessary to succeed in the IELTS Listening test.